Law Enforcement Against the Criminal Act of Prostitution in Moroseneng City of Surabaya - Eka Putri Novita Sari; Vita Mahardhika; R. K. Wijaya Kusuma (NOVUM : JURNAL HUKUM, 2024)
This study focuses on prostitution practices in the Moroseneng area of Benowo, Surabaya, which, despite having been officially shut down by the local government, continues to operate covertly. Prostitution is considered a morally and legally prohibited act, involving individuals—primarily women—offering sexual services in exchange for money. The research aims to examine the extent of law enforcement efforts in addressing prostitution in Moroseneng and to identify the obstacles hindering effective enforcement. Using empirical legal research, the study involves interviews with Satpol PP officers and sex workers (PSK) in the area. The findings indicate that prostitution activities persist due to economic necessity, as many individuals rely on the practice to meet daily needs. Furthermore, law enforcement is deemed ineffective, primarily because the criminal sanctions imposed fail to deter repeat offenses. The lack of strict punishment and limited follow-up actions allow prostitution to continue in hidden forms. The study concludes that stronger enforcement mechanisms, combined with rehabilitation and economic empowerment programs, are necessary to address the root causes and reduce the recurrence of prostitution in Moroseneng. Additionally, the government should strengthen legal instruments and improve coordination among law enforcement agencies to create a more sustainable and preventive approach.